Clinical profile of oral squamous cell carcinoma patients attending a tertiary care hospital (Bangladesh Medical Journal Khulna, 2015)
Oral cancer is one of the most common cancer and constitute a major public health problem. It is estimated that more than 90% of all oral neoplasms are oral squamous cell carcinoma. The purpose of the study was to evaluate the clinical profile of patients with oral squamous cell carcinoma for gender, age, education, occupation, personal habits, site of lesion and histological grading. Two hundred and sixteen confirmed cases of oral squarnous cell carcinoma were included in this study. It was conducted over a period of two years from July 2009 to June 2011 in the department of Dental Surgery of Khulna Medical College Hospital. Male female ratio was 1.5: 1. Mean age was 50.46 years. Correlation between two variables ie. level of education and histomorphological pattern of the lesion were found to be statistically nonsignificant (P>0.05). The commonest age of presentation was in the fifth decade of life. Most of the cases reported at advance stages of the disease which often leads to delay in the management. Majority of patients (70.73%) presented with well differentiated squamous cell carcinoma. Tobacco chewing was the major cause for the development of oral carcinoma DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22554 Bang Med J (Khulna) 2014; 47 : 3-6